1996
DOI: 10.1126/science.271.5253.1291
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 Langerhans' Cell Tropism Associated with Heterosexual Transmission of HIV

Abstract: 7 P De Togn e t a / , i b~d , p 703, T. A Banks et a1 , J /n?n?uno/ 155, 1685 (1 995) 8 Mce were ~mmun~zed intrapertoneally w~th 100 &I of phosphate-buffered sane contanng 10% SRBCs (22) Ten days later, spleens were harvested, embedded In 0 C.T compound (M~les), and frozen In q u d ntrogen Frozen t~ssue sections (6 to 10 &m th~ck) were f~xed n cold acetone Endogenous per-ox~dase was q~~enched w~th 0 2% H, O, n methanol Sectons were sta~ned by f~rst ncubatng w~t h PNA-b~o t~n (Vector) and w~th rat antserum prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
137
2
3

Year Published

1996
1996
2006
2006

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 317 publications
(145 citation statements)
references
References 16 publications
3
137
2
3
Order By: Relevance
“…41 In addition, previous in vitro work has shown that the HIV virus has the ability to replicate in epithelial Langerhans cells, and that subtype E replicates more readily than does subtype B, 7,42 although not all studies have confirmed this. 43,44 Since epithelial Langerhans cell may be the first to encounter the virus after mucosal transmission, 45 the ability of the virus to grow in these cells might enhance viral transmission and could help explain the epidemiologic findings of increased heterosexual transmission in Thailand and Southeast Asia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…41 In addition, previous in vitro work has shown that the HIV virus has the ability to replicate in epithelial Langerhans cells, and that subtype E replicates more readily than does subtype B, 7,42 although not all studies have confirmed this. 43,44 Since epithelial Langerhans cell may be the first to encounter the virus after mucosal transmission, 45 the ability of the virus to grow in these cells might enhance viral transmission and could help explain the epidemiologic findings of increased heterosexual transmission in Thailand and Southeast Asia.…”
Section: Discussionmentioning
confidence: 99%
“…While HIV-1 subtype E accounts for B10% of cases worldwide, in Thailand more than 90% of sexually transmitted HIV-1 cases are subtype E 2-4 and heterosexual transmission is the major mode of spread via a mucosal route. [5][6][7] It has been calculated that heterosexual transmission occurs five times more frequently per heterosexual exposure in Thailand compared to the US. 8 It has therefore been suggested that there is an increased propensity for transmission of subtype E as opposed to subtype B during heterosexual exposure.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The HIV virus has been demonstrated in vitro to have the ability to replicate in epithelial Langerhans cells (LCs), and there is evidence to suggest that Subtype E more readily replicates than Subtype B (7,8). Because these cells may be the first to encounter the virus after mucosal transmission, the ability of the virus to grow in LCs might enhance viral transmission and may explain the epidemiologic findings of increased heterosexual transmission in Thailand and Southeast Asia (8).…”
mentioning
confidence: 99%
“…Because these cells may be the first to encounter the virus after mucosal transmission, the ability of the virus to grow in LCs might enhance viral transmission and may explain the epidemiologic findings of increased heterosexual transmission in Thailand and Southeast Asia (8). Using the SIV/macaque system, Spira et al (9) reported that the first host cells to be infected were cells of dendritic morphology located in the lamina propria of the vaginal mucosa.…”
mentioning
confidence: 99%